Sindrom Feniksa - Kodrič-Dačić, Eva (Knjižnica, 2011)
Purpose: the period from 1941 to 1950 was a turning point in the history of the present National and university library. At the beginning of the II World War the library (at that time known as the University Library) moved to the new palace, constructed by the architect Jožef Plečnik, to be in 1944 severely damaged by fire. However, it was reconstructed by the end of the decade and its library collections grew from 335.000 to 500.000 volumes. The number of library employees increased from 10 to 58 and the formal recognition of its national functions made it one of the most important national institutions. Methodology/approach: the article is based on archival documents and records of the National and university library from the period of 1941-1950. Results: During and after the war the library had a privileged status which was manifested in furnishing and reconstruction of the building, in the growth of library collections through numerous gifts which were received during and after the war to substitute the burnt collections, as well as in acquisition of library materials from the Federal Collection Centre. Its storages remained intact in spite of the war and the rigid censorship and the library was even allowed to collect and to store forbidden publications. Research limitation: the comparison with other national libraries and a socio-historical theoretical interpretation could be a fruitful continuation of this kind of study. Originality/practical implications: the case study explores the position of national library in the specific socio-political circumstances.
Keywords: Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana; knjižnični fondi; zgodovinski pregledi